2006
DOI: 10.1364/oe.14.003181
|View full text |Cite
|
Sign up to set email alerts
|

A known-plaintext heuristic attack on the Fourier plane encryption algorithm

Abstract: Abstract:The Fourier plane encryption algorithm is subjected to a known-plaintext attack. The simulated annealing heuristic algorithm is used to estimate the key, using a known plaintext-ciphertext pair, which decrypts the ciphertext with arbitrarily low error. The strength of the algorithm is tested by using this estimated key to decrypt a different ciphertext which was also encrypted using the same original key. We assume that the plaintext is amplitude-encoded real-valued image, and analyze only the mathema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 211 publications
(91 citation statements)
references
References 14 publications
0
88
0
2
Order By: Relevance
“…Since the initial values of the 2D SLMM function are used to generate the RPMs in decryption, there is no need to send the whole RPMs to the receiver for decryption, which drastically reduces the amount of key data. It is worth noting that the scrambling parameters SKs1 and SKt1 in step (9) do not need to be saved as secret keys, because they can be calculated from the private keys SPh1 and SPh2 during decryption. In addition, eight grayscale images all of size M×N can be encrypted into one of size 2M×2N, which means the compression ratio of the proposed encryption method can be 1:2.…”
Section: The Proposed Asymmetric Multiple-image Encryption and Decmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the initial values of the 2D SLMM function are used to generate the RPMs in decryption, there is no need to send the whole RPMs to the receiver for decryption, which drastically reduces the amount of key data. It is worth noting that the scrambling parameters SKs1 and SKt1 in step (9) do not need to be saved as secret keys, because they can be calculated from the private keys SPh1 and SPh2 during decryption. In addition, eight grayscale images all of size M×N can be encrypted into one of size 2M×2N, which means the compression ratio of the proposed encryption method can be 1:2.…”
Section: The Proposed Asymmetric Multiple-image Encryption and Decmentioning
confidence: 99%
“…Most of the optical encryption methods can be viewed as symmetric cryptosystems, in which the keys for encryption and decryption are identical [8]. However, earlier studies indicated that these cryptosystems are lacking in security strength, because of the inherently linear property of mathematical or optical transformation, and are vulnerable to various attacks such as chosen plaintext attack [8][9][10][11]. In addition, most schemes mainly focused on single-image encryption, which leads to deficiency in multiple-image encryption and transmission [8].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years there have been a number of proposed attacks [92][93][94][95][96][97] on DRPE-type encryption systems, including those systems that operate exclusively with phase [98,99]. Many of these attacks have shown that by only approximating the key one can get adequate decryption of encrypted images.…”
Section: Optical Image Encryptionmentioning
confidence: 99%
“…In general it is difficult to recover the watermark, f ðx; yÞ, directly from the cyphertext gðx; yÞ without using these two keys. The purpose of the cryptanalysis presented in [4][5][6][7][8] is to retrieve part, or all, of the information of these keys with a priori but incomplete knowledge of the plaintext and/or the cyphertext, and eventually retrieve any plaintext encrypted using the same key-set ½/ðx; yÞ; wðu; vÞ. Collision, on the other hand, involves finding another key-set, ½/ 0 ðx; yÞ; w 0 ðu; vÞ, which will encrypt a different f 0 ðx; yÞ to the same gðx; yÞ, the cyphertext of f ðx; yÞ.…”
Section: Collision Algorithmmentioning
confidence: 99%
“…Recently there have been several studies pointing out that random phase encoding systems are vulnerable to chosen-cyphertext, chosenplaintext and known-plaintext attacks [4][5][6][7][8]. However, to date there is no study on the collision resistance of this technique.…”
Section: Introductionmentioning
confidence: 99%